The Development of Flipbook-Based E-Comics as a Learning Medium for the Entrepreneurship Subject among Ninth-Grade Vocational High School Students - Efendi, Ahmad Ivan; Cahyono, Arie Eko; Ulfa, Noviana Mariatul (Education and Development Research, 2025)
The primary issue addressed in this research is the low level of understanding among Eleventh grade vocational high school students regarding entrepreneurship subjects, which are often perceived as unengaging. To address this problem, the study aims to develop interactive flipbook-based e-comics as learning media to enhance students’ comprehension of entrepreneurial concepts. This research adopts the Research and Development (R&D) approach, specifically employing the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Each phase of the model involves a systematic data collection process, including needs analysis, storyboard creation, and prototype development. The resulting e-comic is expected to serve as a practical and effective instructional tool, thereby supporting and enriching the entrepreneurship curriculum in vocational high schools.